Effectiveness of the U-Niko intervention: Protocol for a cluster randomized controlled trial of a municipal-based tobacco and nicotine cessation intervention for adolescents and young adults - Sofie Bergman Rasmussen; Christina Bjørk Petersen; Mette Rasmussen; Nina Kamstrup-Larsen; Charlotta Pisinger (PLoS ONE, 2025)
Introduction The use of nicotine products among youth is increasing, while existing cessation services remain underutilized. Thus, the U-Niko intervention has been developed to provide an evidence-based, youth-oriented approach for effective nicotine cessation. Methods This protocol describes a two-arm cluster randomized controlled trial of youth aged 16–25 in 55 municipalities in Denmark. Prior to the study a stratified randomization was carried out using the online randomization program Sealed Envelope, allocating 27 municipalities to the U-Niko intervention group and 28 municipalities to the control group (tobacco and nicotine cessation recruitment and counseling as usual). The primary outcomes will measure the effectiveness of all three focus areas in the intervention group compared to the control group: A) the municipal counselors’ self-efficacy in youth cessation counseling, B) the number of recruited youths for cessation counseling, and C) the self-reported 14-day point prevalence of abstinence of youth at six months follow-up. Secondary outcomes are the number of recruited youths in a municipality compared to the previous year, continuous abstinence, and validated 14-day point prevalence of abstinence at six-months follow-up. Discussion By evaluating all three focus areas of the U-Niko intervention, this study aims to provide robust evidence for improving youth cessation interventions at local and national levels. Trial registration The study was registered in ANZCTR (ACTRN12624001470583) on 18/12/2024. The Universal Trial Number is U1111-13-14-6117.